Features of the Formation of the Heart Wall in Early Postnatal Ontogenesis (Eurasian Medical Research Periodical, 2023)
In order to identify the features of morphogenesis in postnatal ontogenesis examined histological structure of different departments and shells in the heart of rats 1-22 days after birth. There alternating periods of acceleration and deceleration of the growth rate increase in the thickness of the atrium and the ventricles. The thickness of the endocardial and epicardial increases less significantly. The growth rate of the ventricular myocardium thickness observed in rats 6 and 16 days of age. Structural changes occur due to the growth of the organism. A special feature of the structure and topography of the heart microvessels is their distribution in the course of the cardiomyocytes and the relationship with the fibrous structures of the connective tissue of cardiomyocytes.